PENGARUH STRES KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) ULP MUARADUA: the effect of work stress and workload both partially and simultaneously on employee performance at PT. PLN (Persero) ULP Muaradua. (Ekonomika, 2023)
The research aims to determine the effect of work stress and workload bothpartially and simultaneously on employee performance at PT. PLN (Persero)ULP Muaradua. The population of this study were 33 employees of PT PLN(Persero) ULP Muaradua. The analytical method used is a quantitative analysismethod using multiple linear regression analysis tools that use validity andreliability tests, as well as t-tests and F-tests. The results obtained in this studyare to explain the calculated t-value X1 work stress is (5,247) greater whencompared with the t table value of (2.042), which means that the Job Stressvariable partially affects Employee Performance and the t count of the X2Workload characteristics of (2.613) is greater than the t table of (2.042) whichmeans that the Workload variable partially affects Employee performance. Whilethe simultaneous testing (F test) of the Work Stress and Workload variables showsthat the F count is (53,649) greater than the F table value (3,316) stating thatsimultaneously work stress and workload affect employee performance at PT.PLN (Persero) ULP Muaradua. The termination coefficient value (R Square) is0.781, this shows that the contribution of the effect of Work Stress and Workloadon Employee Performance is 78.1% while the remaining 21.9% is influenced byother variables such as, fulfillment of needs, differences, achievement of values,fairness , genetic component (cited in Afandi, 2016: 67).